Factors Associated with Breastfeeding Patterns in Western Saudi Arabia: A Literature Review - Shahbar, Anwaar; Eid, Noura M.S. (International Journal of Child Health and Nutrition, 2019)
According to literature initiation of breastfeeding is common but exclusive breastfeeding is last one month post delivery in most Saudi women, where continuation to exclusively breastfeed is still challenging. This review discussed breastfeeding patterns, factors associated, and possible approaches to prolong breastfeeding duration in Saudi Arabia. Our review has shown that the early introduction of formula makes the mixed-feeding the most popular feeding method used among the Saudi population. The most frequent reason reported was insufficient milk followed by medical and lifestyle factors. Younger, employed, and higher-educated women were found to be less likely to breastfeed therefore a greater effort probably is required with those women. According to literature, the Baby-Friendly Hospital Initiative (BFHI) was found to be an effective tool in increasing breastfeeding duration worldwide, in Saudi Arabia only one study has published and found that BFHI is effective in initiating breastfeeding but formula was introduced after hospital discharge. We recommend increasing Saudi women’s confidence about breastfeeding, educating them and introducing other strategies such as peer counselling.